Word of Mouth Intention toward Entrepreneurial Restaurant in Shopping Mall Center Surabaya - Liza Agustina Maureen Nelloh; Carolina Chandra (DeReMa (Development Research of Management): Jurnal Manajemen, 2015)
A shopping mall center as the strategic place to earn profits attracts young entrepreneurs to create new restaurants as their businesses in Surabaya nowadays. This research proposed to see the effectiveness of building a new venture in the shopping mall through a test of word of mouth intention with its antecedents (customer satisfaction, perceived price, service quality, and food quality). To test the hypothesis, the researchers used PLS (Partial Least Square). The result of this research indicated that only perceived price and service quality have significant and positive effect on customer satisfaction, thus food quality had no significant effect on customer satisfaction. Moreover, customer satisfaction had significant and positive effect on word of mouth intention toward the restaurant. Managerial implications of this study will encourage young entrepreneurs to increase the menu, the taste and the variation of the food to improve food quality of his or her new restaurants in a shopping mail center.